2017
DOI: 10.1158/0008-5472.can-17-0682
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Protein Coding Mononucleotide Microsatellites in Microsatellite-Unstable Colorectal Cancer

Abstract: Approximately 15% of colorectal cancers exhibit microsatellite instability (MSI), which leads to accumulation of large numbers of small insertions and deletions (indels). Genes that provide growth advantage to cells via loss-of-function mutations in microsatellites are called MSI target genes. Several criteria to define these genes have been suggested, one of them being simple mutation frequency. Microsatellite mutation rate, however, depends on the length and nucleotide context of the microsatellite. Therefor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…Additionally, we investigated mutation profiles in a cohort of MSI endometrial cancers (MSI ECs; n=14). In agreement with previous reports (23,27), our results show that the load of indels at cMS in MSI CRC and EC is high and that multiple concomitant indels at several cMS in the same tumor are very common. Although most CRC and EC were distinguishable based on the cMS mutation patterns, a large set of cMS mutations were shared by the majority of MSI CRC and/or MSI EC (Fig.…”
Section: Cms Mutation Frequencies In Msi Crc and Ecsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, we investigated mutation profiles in a cohort of MSI endometrial cancers (MSI ECs; n=14). In agreement with previous reports (23,27), our results show that the load of indels at cMS in MSI CRC and EC is high and that multiple concomitant indels at several cMS in the same tumor are very common. Although most CRC and EC were distinguishable based on the cMS mutation patterns, a large set of cMS mutations were shared by the majority of MSI CRC and/or MSI EC (Fig.…”
Section: Cms Mutation Frequencies In Msi Crc and Ecsupporting
confidence: 93%
“…We ruled out a potential influence of cMS length, a well-known factor influencing the likelihood of indel mutations on the observed mutation frequency ( Fig. S54), (23,27,39) further supporting the concept of immunosurveillance-induced negative selection. Despite the statistically significant negative correlation between GELS and mutation frequency, we also observed some outliers ( Fig.…”
Section: Immunoselection During Msi Carcinogenesismentioning
confidence: 65%
See 1 more Smart Citation
“…Although many of the recurrently mutated coding microsatellites have been reported by whole genome or exome sequencing studies ( Supplementary Table 7) (13,14,20,27), our analysis identified new genes with recurrently mutated microsatellites.…”
Section: Recurrently Mutated Microsatellites In the Coding Regionmentioning
confidence: 75%
“…MSI results from biallelic inactivation of one of the MMR genes [13]. MSI, as one of immunogenic subtype in Colorectal cancer, has been exploded in research paper [14,15].…”
Section: Dendritic Cells Mast Cells Natural Killer (Nk) Cells Naivmentioning
confidence: 99%